Palliative sedation in Germany: How much do we know? A prospective survey - Jaspers, Birgit; Nauck, Friedemann; Lindena, Gabriele; Elsner, Frank; Ostgathe, Christoph; Radbruch, Lukas (Journal of Palliative Medicine, 2012)
Background: Little is known about the practice of palliative sedation (PS) in Germany. This paper presents an analysis of sedation-related data obtained from the German standardized core documentation system (HOPE) for palliative care patients. Methods: HOPE was complemented by an optional module on ethical decision making (EDM) which was pretested in 2004, data was collected in 2005-6 during the annual 3-month census. Data was analyzed descriptively from palliative care units (PCU - representative) and inpatient hospice (H - non-representative control group). Chi 2 test was used to test for differences between the reported data per item and year within one kind of setting (significance level p ≤ 0.05). Free-text entries were categorized inductively. Results: Datasets were obtained for 1,944 patients (P) with EDM. PS was performed in 13.0/11.8% (2005/2006) P in palliative care units (PCU) and 25.5/22.9% in hospices (H). Main reasons for PS in PCU were dyspnea, pain, fear or anxiety, in H reasons were inconsistent, high prevalence of psychosocial reasons. Most PS in PCU and about half of the PS in H were intermittent. Sedated P were younger than non-sedated. Only 7 P received PS after asking for euthanasia. The most used medication was midazolam. Conclusions: This study reveals a first insight into the use and practice of PS in German PCU and H. For a more detailed systematic survey into the course of decision-making and procedures, a new complementary optional module on PS is being developed by the HOPE group. © Copyright 2012, Mary Ann Liebert, Inc.
CRIS-Team Scopus Importer:2025-10-27